Harnessing nanotechnology for cardiovascular disease applications - a comprehensive review based on bibliometric analysis. (June 2022) - Zheng, Zaiyong; Zhu, Shuang; Lv, Mingming; Gu, Zhanjun; Hu, Houxiang
Abstract: Cardiovascular diseases (CVDs) remain the leading cause of health problems worldwide. Nanotechnology, based on its unique properties, provides novel solutions to the diagnosis and therapy of CVDs. In order to identify and further promote the development of nanotechnology in CVDs, we here provide a comprehensive review of this important field by using the method of bibliometric analysis. In this review, an overview of the publication trends, countries/institutes, referenced sources, and research hotspots of all the literature about nanotechnology in the CVD field are identified and analyzed. Further, a comprehensive review of the major biomedical applications of nanotechnology in CVDs including diagnosis (biosensor and imaging) and therapy (drug delivery and tissue engineering) are provided. Finally, the limits and future prospects of nanoparticles in CVDs are proposed. This review aims to help readers to grasp the general research trends of nanotechnology in CVD applications and to further promote the development of this important field. Graphical Abstract: ga1 Highlights: This work presents a comprehensive review regarding nanotechnology in cardiovascular disease (CVD) applications via the aid of bibliometric analysis method. Publication trend regarding annual growth, most influential countries/institutions, publication-related journals and research hotspot of the nanotechnology-CVD field are identified. The major biomedical applications of nanotechnology in CVDs include diagnosis (biosensor and imaging) and therapy (drug delivery and tissue engineering). Recent advances are illustrated with representative examples from a clinical perspective.